Developing a recovery college: a preliminary exercise in establishing regional readiness and community needs. (4th March 2017) - Kelly, Joy; Gallagher, Stephen; McMahon, Jennifer
Abstract: Background : Recovery orientated intervention has experienced a paradigm shift towards stakeholder training and education within recovery colleges. Such colleges are typically underpinned by a culture of emancipatory education that aims to facilitate recovery through educational choice. Aims : The study aims to establish regional readiness for a recovery college. Specifically, we aim to uncover key stakeholder attitudes towards recovery, outline a contextual conceptualization of recovery and show how inductive, community-based research can incorporate stakeholder views with core fidelity markers of a recovery college. Method : A mixed methods approach, specifically a cross-sectional survey, was adopted to intersect quantitative scales of stakeholder attitudes and qualitative assessment of recovery concepts and community needs. Results : Stakeholders' recovery attitudes were positive overall with some variation between participant groups. Concepts of recovery were developing independent abilities, establishing connectedness to support and as a journey. The needs cited by the stakeholders were largely correlated with the core fidelity markers of a recovery college. Conclusion : A community psychology approach offers a means to ascertain regional readiness for a recovery college, and uncover key development foci based on community needs. We recommend that service areas adopt a similar approach when considering recovery-orientated service developments.